Recent Developments in Mouse Trauma Research Models: A Mini-Review - Gihring, Adrian; Gärtner, Fabian; Schirmer, Melanie; Wabitsch, Martin; Knippschild, Uwe (Frontiers in Physiology, 2022)
The urgency to investigate trauma in a controlled and reproducible environment rises since multiple traumas still account for the most deaths for people under the age of 40. The most common multiple traumas include head as well as blunt thorax trauma alongside fractures. Available therapeutic interventions for these kinds of injuries are very limited due to inadequate understanding of the immediate immune response involving complex host responses. Investigation of these underlying mechanisms call for established animal models to generate reproducible, standardized and at the same time clinically relevant models. Generally, the researcher’s choice are mice to set up murine trauma models. This mini review aims to summarize and list established and published mouse models in the field of trauma research developed to mimic clinically relevant situations.